Psychopharmacology in cancer care : a guide for non-prescribers - Roth, Andrew J.; Nelson, Christian J. (New York, NY : Oxford University Press, 2021)
This volume guides clinicians in facilitating the improved treatment of emotional distress in cancer patients through psychopharmacologic intervention. It is designed for both prescribing and non-prescribing clinicians in psychosocial oncology, psychiatry, psychology, oncology, and palliative care.
Previously issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 18, 2021).
Keywords: Cancer -- Patients -- Mental health; Depression, Mental -- Chemotherapy; Psychopharmacology